Efficacy and safety of Tian Meng oral liquid for the treatment of insomnia: A protocol for systematic review and meta-analysis. Issue 32 (13th August 2021) - Liu, Xinyu; Yang, Jiguo; Zhang, Lu; Li, Runmin; Li, Bingchen; Ge, Xin; Liu, Yuanxiang
Abstract: Background: The incidence of insomnia is very high and seriously affects the lives of its patients. Long-term insomnia can induce other diseases and even cause sudden death. Tian Meng oral liquid is a type of Chinese patent medicine that has been used in the clinical treatment of insomnia and has certain clinical effects. However, its wide application is limited by the lack of evidence-based medical evaluation. Methods: Using retrieval strategies, randomized controlled trials on Tian Meng oral liquid for insomnia were obtained from China National Knowledge Infrastructure, WanFang, Chinese Scientific Journals Database PubMed, Embase, and Cochrane Library, regardless of publication date or language. Studies were screened based on inclusion and exclusion criteria, and the Cochrane risk bias assessment tool was used to evaluate the quality of the studies. The meta-analysis was performed using RevMan 5.3 and STATA 14.2 software. Ultimately, the evidentiary grade for the results will be evaluated. Results: This study aims to evaluate the efficacy and safety of Tian Meng oral liquid in the treatment of insomnia and to provide a more reasonable option for clinical medication. Conclusion: Our findings will provide a strong basis for the effectiveness and safety of Tian Meng oral liquid in the treatment of insomnia.